2015
DOI: 10.1523/jneurosci.3116-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Spatial Stream Segregation in the Ascending Auditory Pathway

Abstract: Stream segregation enables a listener to disentangle multiple competing sequences of sounds. A recent study from our laboratory demonstrated that cortical neurons in anesthetized cats exhibit spatial stream segregation (SSS) by synchronizing preferentially to one of two sequences of noise bursts that alternate between two source locations. Here, we examine the emergence of SSS along the ascending auditory pathway. Extracellular recordings were made in anesthetized rats from the inferior colliculus (IC), the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
34
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 61 publications
7
34
0
1
Order By: Relevance
“…Note that even prior studies using higher (5 mM) muscimol doses found no difference between the effects of muscimol alone vs. its effects when paired with a drug intended to block any action at GABA-B receptors (Happel et al 2014(Happel et al , 2010. Similarly, intracortical blockade of GABA-B receptors had no effect on the ability of neurons in rat A1 to follow trains of acoustic stimuli, i.e., no evidence for forward suppression mediated by GABA-B receptors (Yao et al 2015). Nonetheless, our results do not address the question of whether muscimol at higher doses affects presynaptic receptors in A1, an issue that future experiments will need to resolve.…”
Section: Discussionmentioning
confidence: 83%
“…Note that even prior studies using higher (5 mM) muscimol doses found no difference between the effects of muscimol alone vs. its effects when paired with a drug intended to block any action at GABA-B receptors (Happel et al 2014(Happel et al , 2010. Similarly, intracortical blockade of GABA-B receptors had no effect on the ability of neurons in rat A1 to follow trains of acoustic stimuli, i.e., no evidence for forward suppression mediated by GABA-B receptors (Yao et al 2015). Nonetheless, our results do not address the question of whether muscimol at higher doses affects presynaptic receptors in A1, an issue that future experiments will need to resolve.…”
Section: Discussionmentioning
confidence: 83%
“…We instead propose that short-term synaptic plasticity at interneurons’ inputs, rather than lingering inhibition from the masker tone, mediates the strength and frequency dependence of forward suppression. A more recent study (Yao et al, 2015) infused GABA receptor antagonists into the AC and found no attenuation of forward suppression. However, such antagonists act upon all sources of synaptic inhibition and may conflate the distinct effects of interneuron types observed in the current study.…”
Section: Discussionmentioning
confidence: 97%
“…Neural responses to a sound are often completely abolished when preceded by a spectrally similar sound and more weakly suppressed when preceded by a spectrally dissimilar sound—a phenomenon called forward suppression (FWS) (Brosch and Schreiner, 1997; Calford and Semple, 1995). Although forward suppression is also present subcortically (Malone and Semple, 2001; Schreiner, 1981; Watanabe and Simada, 1971), responses in the auditory cortex (AC) tend to recover more slowly from forward suppression (Fitzpatrick et al, 1999) and are unable to follow fast repetition rates (Creutzfeldt et al, 1980; Miller et al, 2002; Yao et al, 2015), suggesting that forward suppression is enhanced within the AC. How does this enhancement occur?…”
Section: Introductionmentioning
confidence: 99%
“…Spatial sensitivity for stream segregation and forward suppression was increased along the auditory pathway up to the primary auditory cortex providing for separate populations of neurons representing the streams of sounds from the different directions. Application of GABA receptor antagonists to the primary auditory cortex neurons suggested that forward suppression due to depression at the thalamo-cortical synapse is a major factor in auditory stream segregation [61].…”
Section: (C) Stream Segregation By Spatial Cuesmentioning
confidence: 99%